Transforming Collaborative Business Process Models into Web Services Choreography Specifications - Villarreal, Pablo David (2006)
Languages for web services choreography are becoming more and more important for B2B integration. However, the development of web services-based systems is complex and time-consuming. Enterprises have to agree on collaborative business processes and then derive their respective web services choreographies in order to implement B2B collaboration. To support it, this paper presents a MDA approach for collaborative processes. We describe the components and techniques of this approach. We show how collaborative process models defined with the UP-ColBPIP language can be used as the main development artifact in order to derive choreography specifications based on WS-CDL. The transformations to be carried out are also discussed. The main advantage of this MDA approach is that it guarantees that the generated web services choreographies fulfill the collaborative processes agreed between the partners in a business level.